ANALYSIS OF FINANCIAL REPORTS AS PROOF OF PERFORMANCE MEASUREMENT AT PT. GOTO GOJEK TOKOPEDIA TBK IN 2021 - Hijri Juliansyah; Mariayana Br Manik; Sumarni; Muhammad Fahminuddin; Elvira Rose Agave Purba (PT. Radja Intercontinental Publishing, 2023)
Gojek and Tokopedia have united their shared vision and mission by creating a wider market place, more consumers, and greater sales by merging the companies to become PT Goto Gojek Tokopedia Tbk. However, the company's target is not reflected in profits for 2020 and 2021. Therefore, this qualitative descriptive research answers how the financial performance of PT Goto Gojek Tokopedia Tbk in 2021 through various financial analysis, such as current ratio (CR), debt to equity ratio (DER), total assets turnover (TAT), return on assets (ROA), and sales growth (SG). Based on the results of financial ratio analysis calculations, it was found that PT Goto Gojek Tokopedia Tbk in 2021 had good CR, DER and SG ratios. Meanwhile, the ratio of TAT and ROA needs to be evaluated and improved